INDIKASI BATUAN ADAKITIK DI PACITAN, JAWA TIMUR - Baharuddin, Baharuddin; permanadewi, sam (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Volcanic and intrusive rocks from Pacitan area cropping out as lavas, dykes and stockworks, consist of basaltic - andesite to rhyolite in composition. Based on petrologic and geochemical analyses, the volcanic rocks consist of SiO2 55.79 – 72.19%, TiO2 0.07- 0.54%, Al2O3 15.43 – 19.46%, MgO 1.38 – 5.09. While trace element contents, especially Sr 78.25 – 845 ppm, Y 36.31 – 11.15 ppm, Yb 1.05 – 2.58 ppm dan Sr/Y 4.41 – 41.40 ppm. Discriminant diagram of SiO2 vs K2O Pacitan volcanic rocks are including the rocks into tholeiitic low – K series. Therefore in trace element spider diagrams show that the rocks are an island arc affinity except one sample relating with OIB. Several samples of Pacitan volcanics are adakitic like which have high Sr and low Y, Yb content.Key words: petrology, geochemistry, adakitic rocks, Pacitan